One pot molten salt synthesis and photocatalytic studies of magnetically separable copper ferrite microcrystals. (December 2021) - Koppala, Sivasankar; Balan, Ramdas; Litter, Marta I.; Xu, Lei; Li, Kangqiang; Liu, Hua; Lekshmi, I.C.; Mohamed, Rigana Begam
Abstract: The preparation of tetragonal and cubic structured CuFe2 O4 microcrystals by the one-pot molten salt synthesis in a eutectic mixture of NaCl - KCl molten salts at 800–900 °C is reported. Phase evolution and single-phase formation of CuFe2 O4 on temperature and soaking period effect were studied. The structure and morphology of the synthesized compounds were investigated using techniques such as powder X-ray diffraction, Fourier-transform infrared spectroscopy, and scanning electron microscopy. Microscopy studies revealed microcrystals of CuFe2 O4 in an octahedron morphology. Photoluminescence and X-ray photoelectron spectroscopy analysis revealed the existence of surface oxygen defects on both prepared compounds. The photocatalytic studies of tetragonal and cubic structured CuFe2 O4 catalysts shown 89% and 93% degradation of the Rhodamine-B (RhB) dye, respectively, under UV-A (366 nm) irradiation in 90 min. Photocatalytic and magnetic studies indicate that these CuFe2 O4 samples are suitable magnetic separable photocatalysts for efficient dye degradation, and can be reasonably reused. Graphical Abstract: ga1